RUANG PUBLIK DARAT DI KAMPUNG APUNG, JAKARTA BARAT - Petra Yonathan; Gerald Alexander; Damicia Tangyong; Fermanto Lianto (Jurnal Bakti Masyarakat Indonesia, 2022)
From the past until now, urban kampong is often ignored and neglected from the landscape of a city. When viewed physically, the urban kampong is generally known as a settlement that grows in an urban area without any infrastructure planning and urban economic network. Even so, the urban kampong is a residential area in urban areas. The identity of the urban kampong is determined mainly by the activities carried out by its residents. Similar conditions were found in Kampung Apung, Jakarta. A long history, from the construction of warehousing and industry to the elevation of the road as high as 2m, has resulted in the surface of Kampung Apung being lower than Jalan Kapuk Raya. This is supported by the record of land subsidence in Kapuk Village which can reach 3m in 2025. This condition causes the floating village to be inundated with dirty water as high as 1.5 m – 2 m throughout the year. Forcing residents to live in high density, but on the one hand, it is difficult to meet their daily needs to the lack of facilities and public spaces for the community. The Public Space is an example of how the water space, which is the passive space of Kampung Apung can be used for children's play and study space. The Public Space explores the science of simple construction on water through a combination of architectural design and local craftsmanship. Built-in a collaborative and participatory way with many parties so they can learn together and foster a sense of ownership of the results being fought for. Through Participatory Action Research methods, it is hoped that the results of a Public Space Development project can impact the people of Kampung Apung, especially as a place for children to play now and in the future. ABSTRAK: Dari dulu hingga kini, kampung kota sering kali tidak dianggap dan terabaikan dari lanskap sebuah kota. Jika dilihat secara fisik, kampung kota secara umum diketahui sebagai suatu permukiman yang tumbuh di kawasan urban tanpa adanya perencanaan infrastruktur dan jaringan ekonomi kota. Meskipun begitu, Kampung kota yang merupakan kawasan permukiman di perkotaan, identitas yang dimiliki kampung kota sangat ditentukan oleh aktivitas yang dilakukan penghuninya. Kondisi serupa ditemukan di Kampung Apung Jakarta. Sejarah yang panjang mulai dari pembangunan pergudangan dan industri sampai dengan peninggian jalan setinggi 2m, mengakibatkan permukaan Kampung Apung menjadi lebih rendah daripada Jalan Kapuk Raya. Hal ini didukung dengan rekor penurunan muka tanah di Kelurahan Kapuk yang dapat mencapai 3m pada tahun 2025. Kondisi tersebut mengakibatkan Kampung Apung tergenang air kotor setinggi 1,5 m – 2 m sepanjang tahunnya. Memaksa warga untuk tinggal dengan kepadatan tinggi namun di satu sisi kesulitan untuk memenuhi kebutuhan sehari–hari, hingga minimnya fasilitas dan ruang ruang publik masyarakatnya. Ruang Publik Darat menjadi contoh bagaimana ruang air yang menjadi ruang pasif Kampung Apung dapat dimanfaatkan untuk ruang bermain dan belajar anak-anak. Ruang Publik Darat mengeksplorasi ilmu konstruksi sederhana di atas air melalui gabungan desain arsitektur dan ketukangan lokal warga setempat. Dibangun dengan cara yang kolaboratif dan partisipatif dengan banyak pihak sehingga dapat secara bersama-sama belajar serta menumbukan rasa kepemilikan akan hasil yang diperjuangkan. Melalui metode Participatory Action Research diharapkan hasil dari sebuah proyek Pembangunan Ruang Publik Darat dapat memberikan dampak bagi masyarakat Kampung Apung, terutama sebagai tempat bermain anak-anak di masa sekarang dan yang akan datang.